Activation energy for the oxidation of Malaysian coal chars - Haji-Sulaiman, M.Z.; Aroua, M.K. (Journal of the Institute of Energy, 1997)
The oxidation of two Malaysian coal chars has been studied by means of a thermal gravimetric analyser (TGA). The weight-loss data were analysed by the Temperature Program Reaction (TPR) technique, which employed the random pore model of Bhatia & Perlmutter1. All experiments were conducted within a temperature range of 698-773 K (isothermal condition) and heating rates of 2-10 K min-1 (dynamic condition) with char samples in the size range 53-75 μm. It was found that the random pore model can accurately describe the oxidation of char to yield activation energy that is similar to that obtained from model free kinetics, provided the structural parameter ψ, which is an input to the model, is taken as an adjustable parameter.